Neuroblastoma of the Bone and Bone Marrow Without an Apparent Primary Site: Report of 4 Cases With Long-term Follow-up. (July 2019) - Rainusso, Nino; Seghers, Victor; Egler, Rachel; Hicks, John; Russell, Heidi V
Children with neuroblastoma rarely present with metastatic disease without identifiable primary tumors. We describe the clinical and histopathologic characteristics of 4 patients aged 1, 7, 7, and 11 years with neuroblastoma involving bone or bone marrow without an apparent primary site. One patient presented with a periorbital bone lesion, 1 presented with a distal femoral lesion, and 2 presented with diffuse bone marrow involvement. All tumors were negative for MYCN amplification. All patients were alive without evidence of disease 5 years after completion of multimodality therapy. Patients with neuroblastoma of the bone and bone marrow without an apparent primary site may constitute a unique group characterized by older age at diagnosis, nonamplified MYCN tumors, and good response to treatment.